Pembelajaran dan Pendidikan Islam pada Anak Berkebutuhan Khusus (ABK) Attention Deficit Disorder (ADD) pada Sekolah Inklusi - Wicun, Dina; Faturrahman, Faturrahman; Hilyatasnim, Itsna (MASALIQ, 2022)
Doesn't God never discriminate against us? As with education, anyone can study with different physical conditions and mental conditions. Inclusive education that has developed in Indonesia today is a solution to overcome social problems of children with disabilities. Schools that accept children with special needs provide educational services according to their specialty, so that all children have the right to get their rights in the world of education. With this inclusive school education, it unites differences in togetherness.